# Deriving the Triple Product/Cyclic Chain Rule from the limit definition of the partial derivative

I'm trying to derive the Triple Product/Cyclic Chain Rule from the limit definition of the partial derivative, and am wondering if someone could help me please?

I state the Rule as follows following wikipedia:

Given a function $$G(x,y,z)=0$$, and assuming that the conditions of the Implicit Function Theorem hold, we may write $$x=x(y,z)$$, $$y = y(x,z)$$, and $$z=z(x,y)$$. Then:

$$\bigg (\frac{\partial x}{\partial y} \bigg )_{z= \bar{z}} \bigg (\frac{\partial y}{\partial z} \bigg )_{x= \bar{x}} \bigg (\frac{\partial z}{\partial x} \bigg )_{y= \bar{y}} = -1$$

Re-writing each of the partial derivatives in terms of a limit quotient, the expression on the left hand side becomes:

$$\lim_{\Delta y \to 0} \frac{x(y+\Delta y,\bar{z})-x(y,\bar{z})}{\Delta y}.\lim_{\Delta z \to 0} \frac{y(\bar{x},z+\Delta z)-y(\bar{x},z)}{\Delta z}.\lim_{\Delta x \to 0} \frac{z(x+\Delta x,\bar{y})-z(x,\bar{y})}{\Delta x}$$

And so my question is how do we get from this expression to $$-1$$?

I've thought that perhaps the $$\Delta x, \Delta y$$ and $$\Delta z$$ are related in a way that involves a minus sign, but beyond that am stuck. Guidance gratefully received.